Kesenjangan Gender Dalam Pewarisan: Praktik, Hambatan, Dan Reformasi Dalam Kompilasi Hukum Islam Dan Perdata Barat - Rayi Kharisma Rajib; Ahmad Aufa Tsaqif; Sergio Alonso Selan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines gender disparities in inheritance distribution, contrasting practices under Indonesia's Compilation of Islamic Law (KHI) and Western civil law frameworks. Traditional KHI provisions allocate fixed shares typically half for daughters versus sons rooted in patriarchal interpretations, perpetuating economic inequality and limiting women's property rights. Western civil law, emphasizing equality, offers models like equal division or testamentary freedom, yet faces cultural resistance in pluralistic societies. Key barriers include socio-cultural norms, religious dogma, and legal harmonization challenges, exacerbating marginalization of female heirs. Drawing on comparative analysis and empirical cases from Indonesia, the research proposes reforms: progressive reinterpretation of Quranic principles, legislative amendments for gender-neutral shares, and hybrid models integrating equity with faith-based values. These strategies aim to foster inclusive inheritance systems, advancing human rights and sustainable family equity.